(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to apply the Montessori method based on recycling in Tambakasri Village, Malang, East Java, to address children’s speech delay through sustainable education. Conducted on July 30, 2025, at the Tambakasri Village Hall, the program involved 30 participants, including children, parents, educators, and health cadres. The initiative emphasized self-directed learning using recycled household materials such as eggshells, cardboard, and paper to stimulate language, motor, and cognitive development. Evaluation was conducted through observation and participant feedback. The results showed that recycled Montessori-based learning significantly improved children’s communication skills, creativity, and environmental awareness. This initiative demonstrates how low-cost, eco-friendly Montessori practices can enhance early childhood development while promoting sustainability in rural communities.